REPRESENTASI PERAN IBU DALAM FILM NGERI-NGERI SEDAP: ANALISIS SEMIOTIKA ROLAND BARTHES - Zahra, Misyka; Ramadhan, Naufal Habib; Al Farisi, Rayhan Salman; Ardiyanto, Erik (Program Studi Ilmu Komunikasi Universitas Paramadina, 2024)
Film